INFORMATION REGARDING AGRONOMIC PRACTICES AND PLANT PROTECTION MEASURES OBTAINED BY THE FARMERS THROUGH ELECTRONIC MEDIA - G. A. Khan; S. Muhammad; K. Mahmood Ch.; M. A. Khan (Journal of Animal and Plant Sciences, 2013)
Agricultural sector is exposed to various hazards related to production and protection of crops. However, timely information can pave the way towards uplifting this important sector. In this context, role of electronic media is very critical for keeping the farming community updated by providing them relevant agricultural information. The research paper focuses on the agronomic and plant protection spheres of agricultural information covered by electronic media and effectiveness thereof. The study was conducted in district Faisalabad (mix cropping zone).The data were collected through an interview schedule from 330 randomly selected respondents. The findings of the study showed that as a whole, electronic media played comparatively better role in the context of agronomic practices as compared to plant protection measures.
Keywords: Electronic media; agronomic practices; plant protection measures